Maturity model based on CMMI for governance and management of Green IT. Issue 6 (1st December 2019) - David Patón-Romero, J.; Baldassarre, Maria Teresa; Rodríguez, Moisés; Piattini, Mario
Abstract : Sustainability is a problem that is increasingly worrying organisations around the world, which has led them to adopt sustainable practices in their processes. From the point of view of one of the areas that have had the greatest impact in recent times in organisations, the area of information technology (IT), different sustainable practices have arisen in isolation, known as Green IT practices. So, a framework that organises and establishes these practices (until now isolated) is necessary in order to implement, assess, and improve the Green IT in organisations in an efficient, gradual, and integrated way. In this study, the authors propose a maturity model based on capability maturity model integration (CMMI), through which it is intended to help organisations gradually implement and improve through different levels of maturity, the governance and management of Green IT. The validations of this proposal carried out through experts and practical cases demonstrate the usefulness of this proposal when implementing, assessing, and improving the Green IT in organisations.